Function of permeable geosynthetics in unsaturated embankments subjected to rainfall infiltration. Issue 2 (1st April 2007) - Gallage, C. P. K.; Uchimura, T.; Garcia, E. F.
Abstract : ABSTRACT This paper presents laboratory tests and experiments using scale models to study the hydraulic behavior of permeable geosynthetics within unsaturated embankments subjected to rainfall infiltration. Water retention curves were measured in the laboratory in order to evaluate the unsaturated hydraulic characteristics of soil and geosynthetics. Model embankments were built using two layers of permeable geosynthetics; rainfall was simulated using an irrigation pipe. Embankments were subjected to wetting and drying processes; negative and positive pore water pressure and water contents within the model were measured. Comparison between Tempe pressure cell and hanging column test results showed that geosynthetics embedded within the soil approached saturation only when the pore water pressures of the surrounding soil were close to zero or positive. This behavior was also observed in the model tests. Local failure during the wetting processes was observed while pore water pressure increased immediately above the geosynthetic layers. In the models, where strips of geotextile were used, water could not accumulate above the geotextile, and instead drained down between strips. Strips of geotextile prevented the capillary barrier effect and allowed the free drainage of water through the embankment.